POST-COMPOSTING NUTRITIONAL SUPPLEMENTATION. FOR INCREASED MUSHROOM YIELD - J. N. KAPOOR, B. L. DHAR* AND (Indian Phytopathology, 2002)
Supplementation with formalin treated soybean meal at casing was tried under Indian growing conditions. Supplement used was 3 and 10 per cent of dry weight of compost. An increase of 15 per cent in mushroom yield over unsupplemented control was obtained.